A historical perspective on water governance in Republic of Ireland - Hammond Antwi, Sarpong; Linnane, Suzanne; Rolston, Alec; Getty, David; H. Slinger, Jill (International Journal of Water Governance, 2023)
This paper provides a historical perspective on the evolution of water governance in the Republic of Ireland where long-term shifts in agricultural activities, demographic characteristics, water and debates over drinking water supply charges have influenced water resources governance and the integration of management practices. Drawing on threads from the past, the paper first describes how water governance from the early 1950s focused on rural access to water, pollution control and monitoring. With the advent of the Water Framework Directive in 2003, the crux of policy and management practices changed, with 81% of present policies mirroring Integrated Water Resource Management principles. However, issues such as the implementation of drinking water supply water charges and equitable access to water resources remain controversial. Looking to the future, the effects of climate change and land use planning, as well as demographic changes and international legislation are among those factors influencing water policy and management in the Republic of Ireland. Structured stakeholder engagement and further research directed at improving water quality is advocated to promote a sustainable and equitable water future.